Silver Doped TiO2 Nanostructure Composite Photocatalyst Film Synthesized by Sol-Gel Spin and Dip Coating Technique on Glass - Mojtaba Nasr-Esfahani; Mohammad Hossein Habibi (International Journal of Photoenergy)
New composite films (P25SGF-MC-Ag, MPC500SGF-MC-Ag, and ANPSGF-MC-Ag) have been synthesized by a modified sol-gel method using different particle sizes of TiO2 powder and silver addition. Nanostructure TiO2/Ag composite thin films were prepared by a sol-gel spin and dip coating technique. while, by introducing methyl cellulose (MC) porous, TiO2/Ag films were obtained after calcining at a temperature of 500°C. The as-prepared TiO2 and TiO2/Ag films were characterized by X-ray diffractometry, and scanning electron microscopy to reveal the structural and morphological differences. In addition, the photocatalytic properties of these films were investigated by degrading methyl orange (MO) under UV irradiation. After 500°C calcination, the microstructure of MC-TiO2 film without Ag addition exhibited a microstructure, while significant sintering effect was noticed with Ag additions and the films exhibited a porous microstructure. Nanostructure anatase-phase TiO2 can be observed with respect to the sharpening of XRD diffraction peaks. The photodegradation of porous TiO2 deposited with 5×10−4 mol Ag exhibited the best photocatalytic efficiency, where 69% methyl orange can be decomposed after UV exposure for 1 hour.